ANALISIS PENGARUH PERTUMBUHAN EKONOMI, INFLASI, NILAI TUKAR, DAN SUKU BUNGA TERHADAP PERTUMBUHAN PENYALURAN KREDIT DI BANK NASIONAL YANG TERDAFTAR DI INDEKS LQ45 PERIODE TAHUN 2020–2024 - Purba, Henry; Malau, Harman; Siagian, Harlyn (POLITEKNIK LP3I JAKARTA, 2026)
This study examines the impact of economic growth, inflation, exchange rates, and interest rates on credit growth in national banks listed in the LQ45 Index during the 2020–2024 period. The analysis focuses on national banks that consistently remained constituents of the LQ45 Index, representing highly liquid, large-capitalization, and systemically important banks in the Indonesian economy. The observation period covers both the economic downturn during the COVID-19 pandemic and the subsequent recovery and monetary policy normalization, providing a relevant context to assess the sensitivity of bank lending to macroeconomic dynamics. Macroeconomic data are obtained from official publications of Statistics Indonesia and Bank Indonesia, while banking credit data are sourced from national banking statistics and published reports. At the aggregate level, Indonesia’s banking credit exhibited a strong upward trend throughout the study period, with LQ45 banks accounting for a substantial share of total national credit. This study is expected to contribute empirical evidence on how dominant banks adjust their lending behavior in response to macroeconomic changes and to provide insights for policymakers, bank management, and investors.